Analysis of Factors Influencing the Grading of Condition Severity and Zoning Management in an Emergency Triage System - Yongxia SUN; Xiuping WANG; Huiping XUE; Xiuzhen LI (Tehran University of Medical Sciences, 2017)
Background: To identify and analyze factors that influence the grading and zoning management model of emergency triage as a first step in the improvement of the system. Methods: Questionnaires were used to extract data from clinical histories of 286 patients who attended the Emergency Department of Binzhou Central Hospital (Binzhou City, Shandong Province, China) from September to November of 2015. Through logistic regression analysis, influencing factors for unreasonable (≥ 2h) emergency department retention times were identified. Results: Analysis of general characteristics of patients including gender, method of payment or assigned medical department did not result in any statistically significant differences between patients with a time to discharge longer than 2 h and those with a shorter time to discharge (P＞0.05). Older age, higher income, lower or higher education degree, admission time from 17:00-7:59, and lack of understanding of zoning management and of condition severity grading resulted in a retention time greater than or equal to 2 hours (P < 0.05). According to the Logistic regression model: age, income level, education degree, admission time, degree of understanding of zoning management and condition severity grading were all independent risk factors affecting the time to discharge from the emergency department (P＜0.05). Conclusion: Countermeasures need to be developed in order to minimize the influence of patients' factors and promote reasonable average retention times lower than 2 hours in the emergency department.